Răspuns :
Răspuns:
[tex]\boldsymbol{ \red{b) \ 4\sqrt{5} - 8 }}[/tex]
Explicație pas cu pas:
[tex]AB = \sqrt{4^2+4^2} = 4\sqrt{2}[/tex]
Notăm AC = x > 0 ⇒ C∈AB ⇒ CB = AB - AC = 4√2 - x
[tex]AC^2 = CB \cdot AB[/tex]
[tex]x^2 = (4\sqrt{2} - x) \cdot 4\sqrt{2} \Rightarrow x^2 + 4\sqrt{2}x - 32 = 0\\[/tex]
[tex]x=2(\sqrt{10}-\sqrt{2}), \ x=-2(\sqrt{2}+\sqrt{10})[/tex]
Reținem valoarea pozitivă
[tex]AC = 2(\sqrt{10}-\sqrt{2}) \implies BC = 6\sqrt{2} - 2\sqrt{10}\\[/tex]
Scriem ecuațiile:
[tex]\boldsymbol{ AC^2 = (x_A - a)^2 + (y_A - b)^2}[/tex]
[tex][2(\sqrt{10}-\sqrt{2})]^2 = (0 - a)^2 + (4 - b)^2[/tex]
[tex](1) \ \ 48-16\sqrt{5} = a^2 + 16 - 8b + b^2\\[/tex]
[tex]\boldsymbol{ BC^2 = (x_B - a)^2 + (y_B - b)^2}[/tex]
[tex][6\sqrt{2} - 2\sqrt{10}]^2 = (4 - a)^2 + (0 - b)^2[/tex]
[tex](2) \ \ 112-48\sqrt{5} = 16 - 8a + a^2 + b^2\\[/tex]
Scădem (2) din (1)
[tex]48\sqrt{5}-16\sqrt{5}-(112-48\sqrt{5}) = a^2 + 16 - 8b + b^2 - (16 - 8a + a^2 + b^2)[/tex]
[tex]32\sqrt{5} - 64 = 8(a - b)[/tex]
[tex]\implies \bf a - b = 4\sqrt{5} - 8[/tex]